Additive Effects of VDBP and 1,25(OH)2D3 on the Viability and Apoptosis of Rheumatoid Arthritis Synovial Fibroblasts - Zhang, Yeyong; Li, Shufeng; Zhuo, Feng; Wang, Hongxing; Geng, Xiubin; Xu, Bing; Yin, Luxu; Sun, Huaqiang; Yan, Xinfeng (Frontiers in Endocrinology, 2021)
Aim This study is to investigate the additive effect of Vitamin D-binding protein (VDBP) and 1,25(OH)2D3 on the viability and apoptosis of synovial cells from patients with rheumatoid arthritis (RA). Methods Synovial tissues and synovial fluid of patients with RA and osteoarthritis (OA) were collected. The expression of VDBP was analyzed with immunohistochemistry and ELISA. CCK-8 assay was applied to detect cell viability. Flow cytometry was used to analyze cell cycle and apoptosis. Results Immunohistochemical results showed that the expression of VDBP in the synovium of RA patients was significantly lower than that of OA (P<0.05). Similarly, ELISA results presented a lower expression of VDBP in the synovial fluid of RA patients. The results of CCK-8 assay showed that both 1,25(OH)2D3 and VDBP significantly inhibited the viability of rheumatoid arthritis synovial fibroblasts (RASF) (P<0.05). The treatment with 1,25(OH)2D3+VDBP led to more significantly inhibited viability of RASF, compared with 1,25(OH)2D3 alone (P<0.05). The results of flow cytometry showed that 1,25(OH)2D3 and VDBP both promoted the apoptosis of RASF (P<0.05) and 1,25(OH)2D3+VDBP led to a higher proportion of RASF apoptosis, compared with 1,25(OH)2D3 alone (P<0.05). However, 1,25(OH)2D3 and VDBP had no significant effect on the cell cycle of RASF. Additionally, 1,25(OH)2D3 promoted the expression of VDBP in RASF, but not concentration-dependently. Conclusion VDBP is reduced in the synovial tissue and synovial fluid of RA patients and can inhibit viability of RASF and promote the apoptosis of RASF. The 1,25(OH)2D3 can upregulate the expression of VDBP in RASF. Additionally, VDBP can enhance the effects of 1,25(OH)2D3 on viability and apoptosis of RASF.